Trauma Psikologis Tokoh Utama dalam Novel Rumah Untuk Alie Karya Len Liu: Kajian Psikologi Sastra : Psychological Trauma of the Main Character in Len Liu's Novel Rumah Untuk Alie: A Study of Literary Psychology - Prameswari, Shella Sanggam; Yulianto , Bambang (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Literary works often reflect the complexities of life, including trauma and psychological conflict. The novel Rumah untuk Alie highlights the childhood trauma of a girl in a dysfunctional family that shapes her identity and behavior, and addresses systemic violence in a patriarchal family. This study aims to understand the trauma and healing process of the main character as a reflection of the struggle to confront inner wounds, employing a descriptive, qualitative literary psychology approach. Data in the form of narrative excerpts, dialogues, and behavioral descriptions related to trauma and psychological conflict were collected from the novel. The analysis covers trauma identification, interpretation of psychological symptoms, and exploration of the character's healing process based on trauma theory and psychoanalysis, emphasizing the meaning of the traumatic experience for the character's personality. The main character experiences deep psychological trauma due to her mother's loss and family violence, triggering alienation and guilt that manifest as fear, social withdrawal, and suicidal ideation. Despite facing rejection, Alie gradually undergoes self-acceptance and inner healing, demonstrating the struggle from devastation to courage and reconciliation with her past. Besides criticizing patriarchal violence, the story emphasizes the importance of empathy and inner peace.